Influence of Growing Medium and Seed Size on Germination and Seedling Growth of Pinus gerardiana Wall. Issue 2 (2nd April 2016) - Kumar, Raj; Shamet, G. S.; Alam, N. M.; Jana, Chayna
Abstract: Pinus gerardiana Wall. is an important nut-producing pine having restricted distribution in the world. It has been observed that natural regeneration in the species is extremely poor or entirely lacking. The species has erratic and infrequent seed years, dormancy-related problems, and slow growth of seedling, which reduces its regeneration process in natural habitats. Therefore, we investigated the effect of growing medium and seed size on germination and seedling growth of the Pinus gerardiana . The seeds were categorized into two sizes, viz, small (<2.35 cm) and large (>2.35 cm) and five growing medium treatments were used, viz, Soil:Sand:FYM; Soil:Sand:Moss:FYM; Soil:Moss:Vermicompost; Soil:Sand:Vermicompost; and Soil:Sand:Moss:Vermicompost, for assessing their impact on germination and seedling growth. It was observed that, among different growing medium treatments, higher germination and seedling growth parameters were recorded, when Soil:Sand:Moss:Vermicompost was used for the study. Between different seed sizes, higher germination and seedling growth were recorded when seed size was large.